Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A) 2/3 - x - 1/5 = 2/5 - 1/7
2/3 - x - 1/5 = 9/35
2/3 - x = 9/35 + 1/5
2/3 - x = 16/35
x = 2/3 - 16/35 = 22/105
B) 1/2 x X : 2/3 = 1 2/5
1/2 x X : 2/3 = 7/5
1/2 x X = 7/5 x 2/3
1/2 x X = 14/15
X =14/15 : 1/2
X = 28/15
C) 2/5 x X + X x 1/5 = 2/7
X x ( 2/5 + 1/5 ) = 2/7
X x 3/5 = 2/7
X = 2/7 : 3/5 = 10/21
a)1/3+1/4+2/3+3/4
=(1/3+2/3)+(1/4+3/4)
=1+1
=2.
b)1/2+1/3-1/5+1/6
=(1/2+1/3+1/6)-1/5
=1-1/5
=4/5
c)2/3x4/5+1/3x4/5
=4/5x(2/3+1/3)
=4/5x1
=4/5
d)2/3x4/5-1/3x4/5
=4/5x(2/3-1/3)
=4/5x1/3
=4/15
1 / 5 + x = 3 / 7 + 1 / 3
1 / 5 + x = 16 /21
x = 16 / 21 - 1 / 5
x = 59 / 105
x - 1 / 2 = 2 / 3 - 1 / 5
x - 1 / 2 = 7 / 15
x = 7 / 15 + 1 / 2
x = 29 / 30
3 / 5 * x = 2 / 7+ 1 / 4
3 / 5 * x = 15 / 28
x = 15 / 28 : 3 / 5
x = 25 / 28
7 / 8 : x = 1 / 6 * 2 / 3
7 / 8 : x = 1 / 9
x = 7 / 8 : 1 / 9
x = 63 / 8
\(\frac{1}{2}\times\frac{1}{2}+\frac{1}{2}\times\frac{1}{3}+\frac{1}{3}\times\frac{1}{4}+\frac{1}{4}\times\frac{1}{5}+\frac{1}{5}\times\frac{1}{6}\)
\(=\frac{1}{2\times2}+\frac{1}{2\times3}+\frac{1}{3\times4}+\frac{1}{4\times5}+\frac{1}{5\times6}\)
\(=\frac{1}{2}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+\frac{1}{5}-\frac{1}{6}\)
\(=\frac{1}{2}-\frac{1}{6}\)
\(=\frac{1}{3}\)
1/2-1/2*1/2=1/2-1/4=1/2
3/2+2/3:3/2=3/2+2/3*2/3=3/2+4/9=27/18+8/18=35/18
4/5*5/6:2/3=2/3:2/3=1
4/5:5/6*2/3=4/5*6/5*2/3=24/25*2/3=16/25
\(x.1-\dfrac{1}{2}=\dfrac{2}{5}:\dfrac{1}{3}\)
\(x.1-\dfrac{1}{2}=\dfrac{6}{5}\)
\(x.1\) \(=\dfrac{6}{5}+\dfrac{1}{2}\)
\(x.1\) \(=\dfrac{17}{10}\)
\(x\) \(=\dfrac{17}{10}:1\)
\(x\) \(=\dfrac{17}{10}\)
Vậy \(x=\dfrac{17}{10}\)